Corrosion Science: Modern Trends and Applications - Suresh Kumar, N.; Banerjee, P.; Manjunatha, H.; Chandra Babu Naidu, K. (Bentham Science Publishers, 2020)
The advent of Industry 4.0 has opened a data-rich avenue of predicting and controlling premature degradation of industrial materials. For any industrial construction or manufacturing projects, performing analysis on the structural integrity of materials is crucial for their sustainability. Corrosion Science: Modern Trends and Applications gives scholars a snapshot of recent contributions and development in the field of material corrosion. The book presents 12 chapters that cover topics such as corrosion testing methods, anti-corrosive coating mechanisms, corrosion in different types of products (electronics, polymers), industrial systems (power plants, concrete constructions, and hydraulic systems), and corrosion as a result of environmental characteristics (such as marine surroundings). The breadth of topics covered coupled with the reader-friendly presentation of the book make it highly beneficial for students, research scholars, faculty members, and R&D specialists working in the area of corrosion science, material science, solid-state science, chemical engineering, and nanotechnology. Readers will be equipped with the knowledge to understand and plan industrial processes that involve measuring the reliability and integrity of material structures which are impacted by corrosive factors.